Respuesta :

Simplifying (7 + -2x)(11 + -2x)(x) = 0 Reorder the terms for easier multiplication: x(7 + -2x)(11 + -2x) = 0 Multiply (7 + -2x) * (11 + -2x) x(7(11 + -2x) + -2x * (11 + -2x)) = 0 x((11 * 7 + -2x * 7) + -2x * (11 + -2x)) = 0 x((77 + -14x) + -2x * (11 + -2x)) = 0 x(77 + -14x + (11 * -2x + -2x * -2x)) = 0 x(77 + -14x + (-22x + 4x2)) = 0 Combine like terms: -14x + -22x = -36x x(77 + -36x + 4x2) = 0 (77 * x + -36x * x + 4x2 * x) = 0 (77x + -36x2 + 4x3) = 0 Solving 77x + -36x2 + 4x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(77 + -36x + 4x2) = 0 Factor a trinomial. x((7 + -2x)(11 + -2x)) = 0
-x-7=-2x-11
   +7       +7 

-x= 2x-4
+2x+2x

x=-4